Racism in the Green Book Movie Script by Peter Farelly - Subiyakto, Dimas; Rusmana, Dadan; Priyawan, Pepen (Universitas Pahlawan Tuanku Tambusai, 2025)
Racism is still a prevalent problem in society and is frequently examined in literature and film. Few studies have looked at how racism is created and expressed via characterization in movie scripts using literary frameworks, despite the fact that many have tackled it from historical and sociological viewpoints. Using Wellek and Warren's intrinsic and extrinsic literary techniques as well as George M. Fredrickson's theory of racism, this study attempts to examine how aspects of racism are portrayed in the film script Green Book through the portrayal of its central characters. The study uses a descriptive qualitative approach to find dialogues and settings that illustrate social inequality, racial prejudice, and the formation of racial identity. While previous research has explored the script of this film but they have not directly discussed the elements of racism that occur in this film, this study can bring the theme of racism deeper into the field of narrative and characterization.